Recommendation of Sustainable Landuse in Border Area East Kalimantan-Malaysia - HIDAYANTO, M; SABIHAM, SUPANDI; YAHYA, S; AMIEN, LE ISTIQLAL (Indonesian Center for Agriculture Land Resource Development, 2008)
Development problems of agriculture on border area require handling which more comprehensive and sustainable. Up to now, research results indicate that efforts has been done in handling various problems in agricultural sector, but still partial and is not be able to overcome complex problems. Therefore to overcome various development problems of agriculture on the border area need to be done in holisticaly, covers all aspect i.e. social, economics, ecology, and institution. Sebatik Island is one of state border area between Indonesia and Malaysia, located in Nunukan District, East Kalimantan Province. Up to now, cocoa is still the priority commodity, but its productivity is relatively low. Based on potency and constraint of land resources in Sebatik Island, sustainable recommendations to increase land productivity of cocoa i.e. (1) land and water conservation management, (2) using organic matter, (3) proportional fertilization, (4) using mulch, (5) integrated crop management, (6) integrated crop-livestock system, and (7) improvement of capacity of farmers institution